Penguatan Kapasitas Kreatif Generasi Muda melalui Workshop Desain Grafis Berbasis Teknologi Aksesibel dengan Pendekatan PLA - Nabila Adenina Zidni Maulida; Avinda Wildatus Sania; Deni Malik (Universitas Islam Raden Rahmat Malang, 2025)
Graphic design skills are an important competency in strengthening the creative capacity of the younger generation in the digital era. However, at the village level, there is still a gap in access to applicable training and the use of learning technology in accordance with local conditions. This Thematic Community Empowerment (PPM-T) activity aims to strengthen the creative capacity of the young generation of Rejoyoso Village through an accessible technology-based graphic design workshop with a Participatory Learning and Action (PLA) approach. The implementation method uses participatory workshops with a learning by doing approach, where participants are involved as active subjects in the process of learning, practice, and collaborative action using the smartphone-based Canva application. The results of the implementation showed an increase in basic graphic design competencies, visual communication skills, and participants' confidence in producing contextual visual works. The participatory learning process also results in collaboration between participants and the formation of a graphic design community as a mechanism for the sustainability of the program. Overall, this activity proves that the application of the PLA approach supported by accessible technology is effective in supporting the capacity building of the young generation of the village and is relevant as a model of sustainable community service Keywords: Community Empowerment, Creative Capacity, Graphic Design, Participatory Learning And Action,